Is There Sufficient Evidence Justifying Limited Access of Jehovah's Witness Patients to Kidney Transplantation?. Issue 1 (January 2021) - Carvalho Fiel, David; Nunes Ficher, Klaus; Bernardi Taddeo, Julia; Linhares Silva, Kamilla; Rosso Felipe, Cláudia; Aguiar, Wilson; Daniel Braz Cardone, Jose; Foresto, Renato Demarchi; Tedesco-Silva, Hélio; Medina-Pestana, José
Abstract : Background: Jehovah's Witnesses (JWs) refuse blood transfusions due to religious issues. This situation may impact kidney transplantation (KT) outcomes in case of hemorrhagic complications. We evaluated demographic characteristics of this population, hematologic safety, and graft outcomes. Methods: This was a retrospective, single-center study comparing KT outcomes in JW patients versus a non-JW control group. Hematologic endpoints included clinical indication for blood transfusion (hemoglobin <7 g/dL), decrease of hemoglobin >2 g/dL or hematocrit >5% in the first week after KT, hemorrhagic complications requiring surgery, and de novo prescription of erythropoiesis-stimulating agents. Secondary endpoints included delayed graft function, treated biopsy-proven acute rejection, renal function, mortality, and graft survival at 12 months. Results: From January 1989 to September 2018, we identified 143 JW (10 pediatric) and selected 142 matched control (non-JW) patients. There were no differences in the incidence of clinical indication for transfusion (13.3% versus 11.3%, P = 0.640), but a higher proportion of non-JW patients received transfusions (2.1% versus 9.2%, P = 0.010). There were no differences in the proportion of patients with decreased hemoglobin concentration, in reinterventions due to hemorrhagic complications, in the use of erythropoiesis-stimulating agents at hospital discharge, in the incidence of acute rejection, in renal function, and in mortality or graft survival rate at 12 months. Conclusions: In summary, this matched control cohort study suggests that, when clinically indicated, blood transfusions can be safely avoided in the majority of JW kidney transplant, who achieve and maintain comparable hemoglobin concentrations during the first year after transplantation compared with non-JW patients. Abstract : Supplemental Digital Content is available in the text.